Production of Kraft Paper from Bamboo (Melocanna baccifera) of Mizoram - Guha, S. R. D.; Bahadur, Om; Mathur, G. M. (Indian Forester, 1980)
The paper describes in detail of the investigations carried out on the production of unbleached and leached grades of pulps from Melocanna beccifera (Syn. Melocanna bambusoides) of Mizoram by sulphate process. Melocanna baccifera is a suitable fibrous raw material for paper making.